Risk Factor to Chronic Disease no Transmitted In Cienfuegos, Cuba 2010. Preliminaries results of CARMEN II - Mikhail Benet Rodríguez; Alain Morejón Giraldoni; Alfredo Dario Espinosa Brito; Orestes Orlando Landrove Rodríguez; Dania Peraza Alejo; Pedro Ovidio Orduñez García (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
Chronic diseases are the leading causes of morbidity and mortality in Cuba, the monitoring of them is an important element to alert health care system on its evolution. The aim of this study was to describe the prevalence of four of the most important risk factors for these diseases during the preliminary data of the second survey of Cienfuegos CARMEN project, with emphasis on the differences with the first survey results. Method: Preliminary results of the second CARMEN survey are presented, corresponding to the first (847) cases measured integrally from a probabilitic and representative sample of the adult population of Cienfuegos City. Studied variables included: hypertension; obesity, measured by the body mass index, smoking and diabetes mellitus. Results: 33.7% of interviewed persons were smokers, slightly lower than the first measurement, obesity BMI> = 30 kg/m2 was 18.8%, almost 8% higher than the baseline survey, the arterial hypertension to 35.5% and diabetes mellitus to 6.8%, both well above the measurement of 2001-2002. Conclusions: the risk factors discussed show that the problem after improving over the past 10 years, and generally worsens the values are much higher than those observed during the first measurement CARMEN.